Corrigendum: First record of the Malaysian Bridle Snake, Dryocalamus subannulatus (Duméril, Bibron & Duméril, 1854), in Myanmar (Reptilia, Serpentes, Colubridae) - Justin Lee; Aryeh H. Miller; Grant M. Connette; Khin Swe Oo; George R. Zug; Daniel G. Mulcahy (Check List, 2020)
Upon final cataloguing and proofing of the entire collection from the expedition reported in this paper, we noticed an error in the exact locality. The correct locality for USNM 581990 should be: Thayawthadangyi Island group; Daung (Don) Island; N side cove (12º 17’ 10” N, 98º 06’ 05” E, WGS84), Tanintharyi Region, Myanmar.